Functional Characterization of Glycoprotein Nonmetastatic Melanoma Protein B in Scleroderma Fibrosis - Palisoc, Pamela J.; Vaikutis, Leah; Gurrea-Rubio, Mikel; Model, Ellen N.; O’mara, Morgan M.; Ory, Sarah; Vichaikul, Sirapa; Khanna, Dinesh; Tsou, Pei-Suen; Sawalha, Amr H. (Frontiers in Immunology, 2022)
Glycoprotein nonmetastatic melanoma protein B (GPNMB) is involved in various cell functions such as cell adhesion, migration, proliferation, and differentiation. In this study, we set forth to determine the role of GPNMB in systemic sclerosis (SSc) fibroblasts. Dermal fibroblasts were isolated from skin biopsies from healthy subjects and patients with diffuse cutaneous (dc)SSc. GPNMB was upregulated in dcSSc fibroblasts compared to normal fibroblasts, and correlated negatively with the modified Rodnan skin score. In addition, dcSSc fibroblasts secreted higher levels of soluble (s)GPNMB (147.4 ± 50.2 pg/ml vs. 84.8 ± 14.8 pg/ml, p<0.05), partly due to increased ADAM10. sGPNMB downregulated profibrotic genes in dcSSc fibroblasts and inhibited cell proliferation and gel contraction. The anti-fibrotic effect of sGPNMB was at least in part mediated through CD44, which is regulated by histone acetylation. TGFβ downregulated GPNMB and decreased the release of its soluble form in normal fibroblasts. In dcSSc fibroblasts, GPNMB is upregulated by its own soluble form. Our data demonstrate an anti-fibrotic role of sGPNMB in SSc and established a role for the ADAM10-sGPNMB-CD44 axis in dermal fibroblasts. Upregulating GPNMB expression might provide a novel therapeutic approach in SSc.